2021
DOI: 10.3389/fonc.2021.677983
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Treatment for Advanced Paraganglioma: Case Report of a Novel SDHD Gene Mutation Variant and Systematic Review of the Literature

Abstract: BackgroundParagangliomas (PGLs) are neuroendocrine neoplasms arising from chromaffin cells of sympathetic or parasympathetic paraganglia. Systemic therapies have been used only in metastatic PGLs. Antiangiogenic agents, such as sunitinib, could be a viable therapeutic choice in the subgroup of patients with SDH-positive PGLs. We describe the case of a man with Familial Paraganglioma Syndrome type 1 (FPGL) related to a novel mutation in SDHD gene treated with sunitinib. Furthermore, we performed a systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Insulinomas, thymic NET, and gastrinomas have the worst prognosis and the highest mortality [5]. Clinical symptoms are related to tumor secretion, since GEP-NETs can be associated with symptoms due to ectopic secretion of hormones (functioning NETs) or either do not secrete any hormones or the products secreted do not cause a clinical syndrome (non-functioning, NF-GEP-NET) (Table 2) [32][33][34][35].…”
Section: Epidemiology Clinical and Pathological Featuresmentioning
confidence: 99%
“…Insulinomas, thymic NET, and gastrinomas have the worst prognosis and the highest mortality [5]. Clinical symptoms are related to tumor secretion, since GEP-NETs can be associated with symptoms due to ectopic secretion of hormones (functioning NETs) or either do not secrete any hormones or the products secreted do not cause a clinical syndrome (non-functioning, NF-GEP-NET) (Table 2) [32][33][34][35].…”
Section: Epidemiology Clinical and Pathological Featuresmentioning
confidence: 99%
“…However, it has been documented that in patients with advanced or unresectable metastatic paraganglioma, radiotherapy is effective in improving symptoms and controlling tumor growth, and higher radiation doses are associated with lower tumor recurrence. [13] In addition, patients with succinate dehydrogenase (SDH)-positive paragangliomas can achieve partial remission after treatment with tyrosine kinase inhibitors [14] ; Sesti et al [15] reported that the multitargeted RTK inhibitor Sunitinib may be a viable treatment option for patients with inoperable paragangliomas. Overall, paragangliomas are clinically rare and the specific efficacy of various adjuvant therapies for paragangliomas still requires extensive clinical data to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review reporting patients with PPGLs treated with Sunitinib, almost half of the patients with malignant PPGLs did not have excess catecholamine secretion, while the remaining patients were with elevated catecholamines [ 20 ]. This phenomenon suggests that it is very interesting to explore the relationship between catecholamine secretion and metastatic progression of PPGLs.…”
Section: Discussionmentioning
confidence: 99%